Исследование РТК лазерной сварки - Черкашин, И. В. (ХНУРЭ, 2012)
Research of RTC of laser welding. Laser welding have many abilities, better then classic welding. But the same time laser welding have many problems, which need solving by the correcting of power or using added systems.
Keywords: лазерная сварка; робото-технологический комплекс